PENGARUH KEDISIPLINAN DAN KEPUASAN KERJA DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING TERHADAP KINERJA PEGAWAI - Faisan Achmad Nasution; Sofiyan Matondang; Nikous Soter Sihombing (JURNAL PROINTEGRITA, 2021)
This research was conducted at the Pirngadi Hospital in Medan. This research was focused on non-medical employees as research objects. Based on the data and reports obtained, the researcher hypothesized that there were four non-medical civil servant behavior that was the cause of the low quality of service, namely discipline, job satisfaction, motivation and performance. These four behaviors are then called variables. Researchers classify the discipline and job satisfaction variables into independent variables, motivation into intervening variables and performance into the dependent variable. This study aims at analyzing how the influence of the independent or independent variables on the dependent or dependent variable, and how the indirect effect of the independent variable through the mediating or intervening variables on the dependent variable. The research data were obtained through primary sources and filling out questionnaires by ninety-six samples. Hypothesis testing used path analysis using statistical analysis software. Based on the results of the path analysis method, it was concluded that the discipline variable had no effect on employee performance while the job satisfaction variable had an influence on employee performance. And indirectly there is an effect of discipline and job satisfaction through motivation on employee performance.